Pengaruh Komposisi Media Hidroponik dan Konsentrasi Pupuk Cair Cucian Beras terhadap Pertumbuhan dan Hasil Tanaman Basil Merah (Ocium Basilicum L.) - Fani Firmanda Sucipto; Sigit Soeparjono (Jember University Press, 2023)
Modification of the nutrient solution in the red basil plant can be done hydroponically, because it is able to stimulate the synthesis of secondary metabolites of the basil plant so that the plant can easily get the necessary nutrients through the addition of nutrient doses. The application of liquid organic fertilizer can help the addition of nutrients, while the use of different planting media is expected to obtain a good combination for the cultivation process. This study used rice washing water with the trademark pandanwangi and a combination of planting media between husk charcoal, sand, and bokashi. This study used a factorial complete randomized design (4x3) and repeated 3 times. The factors used are the concentration of rice laundry liquid fertilizer (P), consisting of 4 levels: (P0) : Control 0%, (P1): Rice washing liquid fertilizer concentration 25%, (P2): Rice washing liquid fertilizer concentration 50%, (P3): Rice washing liquid fertilizer concentration 75%, and substrate media composition factor (Q), consisting of 3 levels: (Q1): Husk charcoal and sand 1:1, (Q2): Husk charcoal and bokasi 1:1, (Q3): Husk charcoal, sand and bokasi 1:1:1. The observation variables in this study are plant height, number of leaves planted, leaf area, fresh weight of leaves, dry weight of leaves, fresh weight of plants, dry weight of plants and volume of roots. Based on the results of research that has been carried out, the results of the treatment obtained The interaction between the composition of the planting media and the addition of liquid fertilizer for rice laundry does not have a noticeable effect on all treatments except the root volume parameter. The composition treatment of the growing medium had an unreal effect on all treatments except plant height and leaf area with recommendations of husk charcoal:sand (1:1) for plant height and husk charcoal:bokasi (1:1) for leaf area. The treatment of adding concentration of liquid fertilizer to rice laundry has a noticeable effect on all treatments except the fresh weight of the leaves and the fresh weight of the plant with the best recommendation in applying the concentration of liquid fertilizer of rice laundry 25% perliter - 50% perliter on each plant.